2008
DOI: 10.1055/s-2008-1062731
|View full text |Cite
|
Sign up to set email alerts
|

Die ambulante Versorgung von Schlaganfallpatienten aus Sicht von Hamburger Hausärzten - eine explorative Studie

Abstract: The care of stroke patients is not only the responsibility of a single group of professionals, but is a rather complex task involving different health-care professionals. The rehabilitation process and the interdisciplinary cooperation need to be further analysed to ensure a good cooperation between health-care professionals and to improve the quality of ambulatory care for stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
(14 reference statements)
0
4
0
2
Order By: Relevance
“…Only half of the treatment recommendations from clinical physicians for outpatient care have actually been carried out a year after patients completed their medical rehabilitation [10] and have returned home. In 2008, Barzel et al gathered general practitioners’ points of views on the topic of follow-up care and found that the problem in outpatient care originates during inpatient care [14]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only half of the treatment recommendations from clinical physicians for outpatient care have actually been carried out a year after patients completed their medical rehabilitation [10] and have returned home. In 2008, Barzel et al gathered general practitioners’ points of views on the topic of follow-up care and found that the problem in outpatient care originates during inpatient care [14]. …”
Section: Resultsmentioning
confidence: 99%
“…This should be included in outpatient care, as stroke is such a complex disease that patients often need therapy from several different medical disciplines [13]. According to general physicians (GPs), stroke patients are not well prepared for their return back home after completing inpatient rehabilitation [14]. This problem has to do with both poor outpatient care provision and partly inpatient care [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Der Übergang von stationärer zu ambulanter Weiterbehandlung nach Schlaganfall in Deutschland wird auch aus der Perspektive der Betroffenen sowie der Leistungserbringer als nicht zufriedenstellend angesehen [3,5].…”
Section: Introductionunclassified
“…Furthermore, it is one of the leading causes of adult disability, which results in necessary constant care for a large portion of stroke survivors leaving the major burden on ambulatory care [4]. Since it is an archetype of a chronic disease, advances in post-acute stroke management prospectively have a significant impact on improving the comprehensive chronic care management while decreasing the societal healthcare costs [5,6].…”
Section: Introductionmentioning
confidence: 99%